2023
DOI: 10.3390/nu15040847
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effect of Increased Tryptophan Intake on Its Metabolism and Mental State of the Elderly

Abstract: The elderly often suffer from sleep disorders and depression, which contribute to mood disorders. In our previous work, we showed that elderly individuals with mood disorders had a lower intake of TRP and recommended a TRP-based dietary intervention to improve the mental state of such individuals. In this work, we assessed the impact of a TRP-rich diet on the mental state of, and TRP metabolism in, elderly individuals with mood disorders. Forty elderly individuals with depression and sleep disorders and an equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…The current study sought to elucidate the mechanism underlying the regulation of muscle fiber type transformation by circRNAs in weaned piglets fed a diet high in Trp. Trp is an essential amino acid that is employed for protein synthesis, and its total concentration in the body is the lowest among all the amino acids; therefore, Trp plays a rate-limiting role in protein synthesis . In addition, Trp is also involved in the kynurenine and 5-HT metabolic pathways and is a substrate for the synthesis of the coenzyme nicotinamide adenine dinucleotide as well as melatonin .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current study sought to elucidate the mechanism underlying the regulation of muscle fiber type transformation by circRNAs in weaned piglets fed a diet high in Trp. Trp is an essential amino acid that is employed for protein synthesis, and its total concentration in the body is the lowest among all the amino acids; therefore, Trp plays a rate-limiting role in protein synthesis . In addition, Trp is also involved in the kynurenine and 5-HT metabolic pathways and is a substrate for the synthesis of the coenzyme nicotinamide adenine dinucleotide as well as melatonin .…”
Section: Discussionmentioning
confidence: 99%
“…Trp is an essential amino acid that is employed for protein synthesis, and its total concentration in the body is the lowest among all the amino acids; therefore, Trp plays a rate-limiting role in protein synthesis. 26 In addition, Trp is also involved in the kynurenine and 5-HT metabolic pathways and is a substrate for the synthesis of the coenzyme nicotinamide adenine dinucleotide as well as melatonin. 27 Trp and its metabolites play important physiological roles in a variety of biological processes associated with cell growth and the maintenance of metabolic homeostasis through the regulation of certain signaling pathways and may contribute to the process of muscle development and myofiber type transformation.…”
Section: Discussionmentioning
confidence: 99%
“…A study in 40 elderly persons with insomnia or depression revealed that patients’ initial dietary Trp intake is low, their urinary excretion of KYNA is unaltered and excretion of KYN and QUIN is high. A prolonged, 12-week intake of 25 mg/kg of Trp daily resulted in mood improvement and increased elimination of Trp but reduced the elimination of KYN and QUIN with urine [ 151 ]. A double-blind, placebo-controlled study showed prominent increases in plasma KYN, KYNA and 5-HIAA, occurring 4 h after the oral administration of a single dose of Trp (6 g) to patients with schizophrenia as well as in healthy individuals [ 152 , 153 ].…”
Section: Dietary Interventionsmentioning
confidence: 99%
“…17 To investigate the safety of Trp, researchers recruited participants to assess the effects of a Trp-rich diet on mental status and Trp metabolism in older adults with mood disorders, in which the participants consumed 25 mg/kg per day for 12 weeks. 18 After the test, correlation analysis showed that Trp, 5-hydroxyindole acetic acid (5-HIAA), and KA might have antidepressant effects, while KYN and quinolinic acid (QA) might have pro-depressant effects. It is also concluded that moderate dietary intake of Trp is beneficial for the mental health of elders with mood disorders by improving the metabolism of Trp.…”
Section: Intake Status and Safety Of Dietary Trpmentioning
confidence: 99%